Urbanização e planejamento urbano na periferia do Brasil: a revisão do plano diretor participativo de São Luís, Maranhão (2014-2021) - Santos, Luiz Eduardo Neves dos (2022)
This work investigates the review-and-update process of the main piece of urban legislation of the São Luís municipality, the Comprehensive Plan, as well as its inherent relationship with urbanization. The main goal is to understand in which manner and under which contexts – whether political, economical, and socio-spatial – the review of the Comprehensive Plan, characterized as a participative one, takes place; how the latter has been built and reformulated through distinct actions and discourses on the city; and what are the impacts of the proposed guidelines on the new territorial uses and urban expansion in the municipality borders. A discussion is made as to why a peripheral space like Brazil, more specifically a territory like São Luís, placed at the margin of the periphery, turns into a new locus for the accumulation of capital enabled by planning mechanisms assembled by state and market actions, giving rise to the representation of new spatial arrangements and new materialities through discursive strategies linked to the notions of development and progress. The Participative Comprehensive Plan of São Luís is effectively presented as the product of a juridical techno-bureaucracy materialized through what is here named a cynical urban planning. Its basic feature is the preparation of the municipal territory, by means of its legal setting, for specific uses, in order to meet the demands of the economic power, which acts in multiple scales and articulates with the constituted political powers, affecting local populations and their modes of living. The spatio-temporal scope of the analyzed phenomenon is supported by the understanding of the planning experiences since the 1930s, the moment in which a technical and scientific approach to thinking the city is first identified. Since then, the urban planning processes in the municipality have been the result of the actions, discourses, and investments of the Brazilian state in its relationship with the economic agents. In order to develop the established research goals, a qualitative case study approach in the realm of Geography was adopted, which is justified by the employment of techniques that allow understanding the nature of the proposed socio-spatial phenomenon in the macro-local scale, as well as the relationships that it establishes with the world through its port structure. The query and analysis of primary and secondary sources is highlighted, including a dense bibliographic review of the subject, research in books, scholarly articles, theses, dissertations, newspapers (both printed and electronic), specialized websites, maps, movies, iconography, as well as the reading and interpretation of urban legislation texts, in order to define the specific analytical categories of the proposed method. Accordingly, three main techniques have been employed in the research: observation, document collecting, andinterviewing. As a whole, they allow for interpreting and comprehending the motivations, interests, conflicts, and discourses due to the distinct agents surrounding the review of the Comprehensive Plan, which reverberate in the concrete reality of the São Luís municipality.